The Role of Female Principals in Early Childhood Education on Children’s Social-Emotional Development in Supporting SDG 4 - Dwi Prasetiyawati Diyah Hariyanti; Sri Suciati; Muniroh Munawar; Irma Yuliantina; Perdana Afif Luthfy (Hadlonah: Jurnal Pendidikan dan Pengasuhan Anak, 2026)
This study investigates the role of female principals in early childhood education (ECE) in fostering children’s social-emotional development toward achieving Sustainable Development Goal 4 (SDG 4). A convergent mixed-method survey was conducted with 164 female ECE principals in Central Java, Indonesia. Quantitative data were analyzed using descriptive statistics, while qualitative responses were examined through thematic analysis to explain contextual challenges. The findings reveal that democratic leadership is the most dominant style (78% “always”), followed by delegative (70%), transformational (68%), and authoritarian leadership (42%). The relatively high use of authoritarian leadership indicates that principals often combine participatory and directive approaches in response to contextual challenges, including limited teacher competence and institutional constraints. The novelty of this study lies in three aspects. First, unlike previous Indonesian studies that mainly focused on teacher performance and administrative effectiveness, this study directly links female leadership styles with children’s social-emotional development outcomes. Second, this study integrates gender-based leadership analysis with the Socio-Ecological Model, emphasizing that children’s development is influenced not only by school leadership but also by collaboration among schools, families, and communities. Third, this study proposes a categorized framework of structural, human resource, and socio-cultural barriers that mediate leadership effectiveness in ECE institutions. The findings demonstrate that leadership effectiveness in ECE cannot be measured solely through managerial success, but through its contribution to holistic child development. This study also challenges the assumption that democratic leadership alone guarantees educational quality, showing that systemic support, teacher readiness, and parental involvement significantly shape leadership outcomes. The study repositions female leadership in ECE as outcome-oriented leadership that prioritizes children’s developmental well-being in line with SDG 4.